Elmer and Super El [anglicky] - McKee, David (Andersen, 2012)
One morning, Elmer hears an "Oh no!" Looking round, he spots Super El who´s in need of Elmer´s hepl. He must get to Aunt Zelda without any of the other animals seeing him and, as usual, it´s up to Elmer to come up with a cunning plan!